Analisis Perbedaan Kurikulum 2013 dan Kurikulum Merdeka dalam Pembelajaran IPS di Tingkat Sekolah Dasar - Siti Halima Sineri; Husain, Alma Pratiwi (Jurnal Pendidikan Dirgantara, 2026)
Social Studies (IPS) learning at the elementary school level plays a strategic role in shaping students’ understanding of social, cultural, and economic life, as well as national values. This study aims to analyze the differences between the 2013 Curriculum and the Merdeka Curriculum in IPS learning, including planning, implementation, the use of methods and media, and the assessment of learning outcomes. The research employed a descriptive qualitative approach with a case study, collecting data from curriculum documents, lesson plans (RPP), syllabi, classroom observations, interviews with teachers and school principals, and student questionnaires. The results indicate that the 2013 Curriculum provides a clear learning structure, detailed lesson plans, and systematic material organization that facilitates teachers, but it is less flexible and less contextualized for students. In contrast, the Merdeka Curriculum emphasizes flexibility, relevance of content to the local context, innovative methods such as project-based learning and blended learning, as well as holistic assessment focusing on critical thinking skills, social literacy, and student character. The implementation of the Merdeka Curriculum can enhance students’ learning interest, active participation, understanding of social concepts, and social awareness; however, its effectiveness depends on teacher readiness, school support, facilities, and consistency in assessment. These findings suggest that selecting an appropriate IPS curriculum should consider a balance between structure and flexibility, content relevance, teacher competence, and supporting facilities.